Ectonucleotidases como marcadores prognósticos no tratamento do câncer de próstata - Gardani, Carla Fernanda Furtado (2022)
Prostate cancer (PC) is the most frequently diagnosed neoplasm in males (except for nonmelanoma skin tumors) and represents the second cause of death in men in the western world. It has long survival periods, however patients, due to a still inadequate risk stratification, suffer from excessive treatments or lack thereof. On the other hand, purines (ATP, ADP and AMP) are signaling molecules that have diverse effects on many biological processes. Ectonucleotidases (CD39 and CD73) constitute a family of enzymes involved in the degradation of nucleotides and in the formation of nucleosides, thus having a key role in extracellular purinergic regulation. The objective of this work was to analyze the biochemical and molecular characteristics of the CD39 and CD73 enzymes in PC, as possible prognostic markers and/or therapeutic targets. Therefore, in the first arm of the study, we retrospectively analyzed tissue samples from 23 patients with PC undergoing treatment at Hospital São Lucas da PUCRS. Quantitatively, we determined the expressions of these ectonucleotides using the TissueFAXSTM Cytometry platform software. The mean age of this group was 65.4 years, with 30.5% of these patients having a low-grade Gleason scale and about 69.5% having intermediate to high-grade scores. Regarding the expressions of CD39 and CD73, there was no significant difference in the different Gleason scores. However, we found a correlation between the Gleason score and the intensity of CD39 positivity. per sample, we observed a p = 0.06 and 0.69, when we correlated with the percentage positive area for CD39. Finally, we compared the expression profile of CD39 and CD73 in the 2 groups and observed that the levels of staining intensity for CD39 are significantly higher than the levels of CD73. In the prospective arm, serum and urine samples were collected from 25 patients followed up at the oncology services in Cruz Alta/RS (COHCA and CACON), at the time of the first consultation at the Service (diagnosis) and after 6 months of treatment, to analyze the profile of ATP, ADP and AMP hydrolysis in the plasma and to determine the expressions of CD39 and CD73 in serum extracellular vesicles (EVs). In this arm, the mean age was 68.6 years, with 20% of patients having low Gleason scores, 52% intermediate and 28% high. The analysis of the results showed that there was no significant difference between the ATPase, ADPase and AMPase activities when the 2 collection times were compared. According to Spearman correlation analyses, we observed that ADP hydrolysis in collection 1 showed positive correlations with TURP and with the Gleason scale, and negative correlation when patients underwent prostatectomy. Regarding serum EVs, we observed a significant increase in CD39 expression, when compared to CD73 (p < 0.05) and/or CD39/CD73 expressions combined (p < 0.01) in collection 1.